Evaluasi Mutu Gliserol Hasil Pemurnian Biodiesel Minyak Jelantah Menggunakan Berbagai Jenis Adsorben - Sihotang, Antonius Jumadi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Biodiesel production produces crude glycerol as a byproduct that cannot be utilized directly because it still contains various impurities. The crude glycerol used in this study had a glycerol content of 72%, a water content of 1.78%, ash content of 16.4%, and a density of 1.08 g/cm³, which indicates that the glycerol quality is still low due to the high water content and inorganic components. This study aims to evaluate the effectiveness of three types of adsorbents, namely activated carbon, zeolite, and bentonite, in improving the quality of crude glycerol from used cooking oil. The purification process is carried out through distillation, acidification, and adsorption stages with adsorbent variations of 5%, 7%, and 9%. Then, the purified glycerol was analyzed based on the parameters of glycerol content, water content, ash content, and density.